Swimming Technology Research
Swimming Technology Research manufactures hardware and software to analyze performance in aquatic activities, such as swimming, aquatic therapy, water aerobics, and rowing. Our product line includes the Aquanex Hydrodynamic Measurement System, the Torpedo Expert System for Competitive Swimming, and WOW - WorkOutWriter. We also offer testing, research, and consulting services. Aquanex is a computerized system that provides instantaneous feedback about the forces exerted during aquatic activities. Aquanex can be used to monitor progress in aquatic therapy. In competitive swimming the data can be used to identify force losses that limit performance, track progress in modifying technique, and reinforce positive elements of technique. Torpedo is a software program that offers many advantages to coaches and swimmers: an automated method for tracking swimmer's accomplishments, a simplified means of identifying factors that limit performance, and an enhanced feedback process with visual and kinesthetic cues. The manual includes suggestions for a technique incentive program that can help make competitive swimming a positive experience. WOW - WorkOutWriter is a graphical workout designer that can greatly expedite workout development. WOW instantly calculates all relevant time and distance information, and offers many features that make it easy to add variety to workouts. Included is an archioves for the workout of the week.